Reform of Corruption Criminal Law: a Study of Corruptor Asset Application Law in Indonesia - Achmad Taufan Soedirjo; Faisal Santiago; Surya Jaya (Journal of Social Research, 2023)
The development of a new criminal law system in Indonesia still aims to reveal the crimes committed, find the perpetrators, and punish them with criminal sanctions, especially "corporate punishment", which includes imprisonment and the death penalty. Meanwhile, the issue of international law development, such as the issue of confiscation of proceeds of crime and tools of crime2, has not become an important component in the Indonesian criminal law system. The purpose of this study is to determine the extent to which the reform of corruption criminal law can be carried out, especially in terms of asset forfeiture of corruptors. The research method used is normative research with a legal approach and conceptual approach. The reform of corruption criminal law must provide a clear definition of asset forfeiture of corruptors. The definition must include various types of assets, both tangible and intangible, which are illegally obtained through acts of corruption. The research method used is normative research with a legal approach and conceptual approach. The results of the discussion show that the reform of corruption criminal law regarding the seizure of corrupt assets can strengthen corruption eradication efforts and improve the existing seizure mechanism. The legal reforms carried out include Law Number 31 of 1999 concerning Eradication of Corruption (PTPK Law); Law Number 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes (TPPU Law); Presidential Instruction Number 3 of 2018 concerning Increasing the Role and Optimizing Community Participation in Corruption Eradication; Government Regulation Number 13 of 2021 concerning Procedures for Forfeiture of Corruption Proceeds.